The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2005
DOI: 10.1111/j.1600-0668.2005.00390.x
|View full text |Cite
|
Sign up to set email alerts
|

Odor and chemesthesis from brief exposures to TXIB

Abstract: This study indicated that the plasticizer TXIB could contribute odor at concentrations in the range of parts-per-billion, but could hardly contribute sensory irritation per se, as alleged in reports of some field studies where TXIB has existed amongst many other organic compounds.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(29 citation statements)
references
References 42 publications
1
28
0
Order By: Relevance
“…The distributions of sensitivity to glutaraldehyde for odor and for feel have similar characteristics to those for other VOCs. For instance, Cain et al (2005) found the distributions for the odors of ethanol and 2,2,4-trimethyl-1,3-pentanediol diisobutyrate (TXIB) for the typical subject (as per Fig. 3, top) to vary over two orders of magnitude, when expressed in terms of concentration necessary to go from weak to strong detection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The distributions of sensitivity to glutaraldehyde for odor and for feel have similar characteristics to those for other VOCs. For instance, Cain et al (2005) found the distributions for the odors of ethanol and 2,2,4-trimethyl-1,3-pentanediol diisobutyrate (TXIB) for the typical subject (as per Fig. 3, top) to vary over two orders of magnitude, when expressed in terms of concentration necessary to go from weak to strong detection.…”
Section: Discussionmentioning
confidence: 99%
“…The variation arises from diVerences in the span of the distributions of sensitivity for the two modalities. For olfaction, the more sensitive modality, the span of concentration between infrequent detection, say 5%, and frequent detection, say 95%, commonly exceeds two orders of magnitude (Cain et al 2005). For chemesthesis, the span may fall below one order of magnitude.…”
Section: Introductionmentioning
confidence: 99%
“…A number of different measures were used in this study. Two of them, the negative mucosal potential, and the ability to specify to which nostril air-phase stimuli are presented, i.e., lateralization, are thought to be dependent upon the trigeminal system (e.g., Cain et al 2005). It was found that normosmics' negative mucosal potential responses to, and intensity judgments of, androstenone were concentration dependent and correlated with the same measures for presentations of the primarily trigeminal stimulus CO 2 .…”
Section: Introductionmentioning
confidence: 84%
“…6 Olfactory detection of TXIB began at concentrations below 1 ppb, with 50% correct detection at 1.2 ppb (comparable detection for ethanol occurred at almost two orders of magnitude higher.) 6 Chemesthetic detection of TXIB began at about 500 ppb, with 50% correct detection at 2.1 ppm for the eye and 4.6 ppm for the nose, both close to saturated vapor concentration (comparable detection for ethanol occurred essentially three orders of magnitude higher.) 6 This shows that plasticizers can be detected by olfactory and chemesthetic detection at very low concentrations.…”
Section: Effect Of Additivesmentioning
confidence: 98%